2014
DOI: 10.1016/j.bspc.2014.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Detection of emotions in Parkinson's disease using higher order spectral features from brain's electrical activity

Abstract: Objective: Non-motor symptoms in Parkinson's disease (PD) involving cognition and emotion have been progressively receiving more attention in recent times. Electroencephalogram (EEG) signals, being an activity of central nervous system, can reflect the underlying true emotional state of a person. This paper presents a computational framework for classifying PD patients compared to healthy controls (HC) using emotional information from the brain's electrical activity. Approach: Emotional EEG data were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
55
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 66 publications
0
55
0
1
Order By: Relevance
“…Research findings on the reason for this are inconclusive. Nine articles discussed the idea of using EEG-based emotion detection to provide assistance, monitoring, assessment, and diagnosis of Parkinson's disease in patients [47,106,107,114,[118][119][120][121][122].…”
Section: Othermentioning
confidence: 99%
“…Research findings on the reason for this are inconclusive. Nine articles discussed the idea of using EEG-based emotion detection to provide assistance, monitoring, assessment, and diagnosis of Parkinson's disease in patients [47,106,107,114,[118][119][120][121][122].…”
Section: Othermentioning
confidence: 99%
“…In order to recognize the depth of rail corrugation easily, bispectrum features need to be extracted. ree amplitude features of bispectrum [21]:…”
Section: Shock and Vibrationmentioning
confidence: 99%
“…In this systematic review, we reported an author (Yuvaraj) who has worked in the emotional field with 4 studies (Yuvaraj, Murugappan, Mohamed Ibrahim, et al, 2014) . In these studies, the emotional stimuli was caused by emotions such us sadness, happiness, fear, anger and surprise.…”
Section: Emotional Eventmentioning
confidence: 99%